A perylene bisimide network for high-performance n-type electrochromism. Issue 93 (3rd November 2016) - Ma, Weitao; Qin, Leiqiang; Gao, Yu; Zhang, Wenqiang; Xie, Zengqi; Yang, Bing; Liu, Linlin; Ma, Yuguang
Abstract : A micro-porous network thin film of core-tetrachlorinated perylene bisimide (PBI) was deposited by electrochemical polymerization, which showed reversible n-doping/dedoping processes at rather low potentials, accompanied by color changes from an orange red (neutral) state to a transparent (radical anion) state and further to an aquamarine (dianion) state. Abstract : A micro-porous network thin film of core-tetrachlorinated perylene bisimide (PBI) was deposited by electrochemical polymerization, which showed reversible n-doping/dedoping processes at rather low potentials, accompanied by color changes from an orange red (neutral) state to a transparent (radical anion) state and further to an aquamarine (dianion) state. The film possesses preferable coloration efficiency and cycling stability (>10 000 cycles).